Doomscrolling and mental well-being in social media users: A serial mediation through mindfulness and secondary traumatic stress - Taskin, Sumeyye; Yildirim Kurtulus, Hacer; Satici, Seydi Ahmet; Deniz, M. Engin (WILEY, 2024)
Considering that large-scale events such as natural disasters, epidemics, and wars affect people all over the world through online news channels, it is inevitable to investigate the impact of following or avoiding negative news on well-being. This study investigated the effect of doomscrolling on mental well-being and the mediating role of mindfulness and secondary traumatic stress in social media users. A total of 400 Turkish adults completed scales to assess doomscrolling, mental well-being, mindfulness, and secondary traumatic stress. The average age of the participants was 29.42 (SD = 8.38; ranged = 18-65). Structural equation modeling was conducted to examine the mediating roles of mindfulness and secondary traumatic stress in the relationship between doomscrolling and mental well-being. Mindfulness and secondary traumatic stress fully mediated the relationship between doomscrolling and mental well-being. The results are discussed in light of existing knowledge of doomscrolling, mental well-being, mindfulness, and secondary traumatic stress. High levels of doomscrolling, which is related to an individual's mental well-being, can predict the individual's distraction from the here and now and fixation on negative news. This situation, in which mindfulness is low, is related to the individual's indirect traumatization and increased secondary traumatic stress symptoms in the face of the negative news he/she follows.
Keywords: doomscrolling; mental well-being; mindfulness; secondary traumatic stress; VALIDATION; Public, Environmental & Occupational Health; Psychology; Social Work